Evaluation of effects of ultrasound-assisted saucing on the quality of chicken gizzards - Haijing Li; Jia Feng; Shuo Shi; Xu Wang; Xiufang Xia (Ultrasonics Sonochemistry, 2022)
The purpose of this study was to evaluate the effects of ultrasound-assisted saucing on the quality of chicken gizzards. The results showed that with the prolonging of the saucing time, the yield, water holding capacity (WHC), lightness (L*), redness (a*) and springiness of chicken gizzards significantly decreased, while the shear force, hardness and chewiness significantly increased (P < 0.05). When the saucing time was the same, the yield, WHC, springiness and tenderness of the ultrasound group were significantly higher than those of the non-ultrasound group (P < 0.05). In particular, when the saucing time was 30 min, the yield, WHC and springiness of the ultrasound group increased by 2.13%, 0.97% and 10.53%, and the shear force decreased by 21.22% compared with those of the non-ultrasound group, respectively. Besides, ultrasound pretreatment increased the content of aromatic compounds, short-chain alkanes, alcohols, aldehydes and ketones, and the principal component analysis displayed that C-50 (saucing for 50 min without ultrasound pretreatment) and U-30 (saucing for 30 min with ultrasound pretreatment) were similar in flavor. Therefore, ultrasound pretreatment is a potential way to improve the quality of saucing chicken gizzards and shorten the processing time.